2020
DOI: 10.3390/molecules25092006
|View full text |Cite
|
Sign up to set email alerts
|

Plant In Vitro Systems as a Sustainable Source of Active Ingredients for Cosmeceutical Application

Abstract: Cosmeceuticals are hybrids between cosmetics and pharmaceuticals which are being designed for a dual purpose: (1) To provide desired esthetical effects and (2) simultaneously treat dermatological conditions. The increased demand for natural remedies and the trends to use natural and safe ingredients resulted in intensive cultivation of medicinal plants. However, in many cases the whole process of plant cultivation, complex extraction procedure, and purification of the targeted molecules are not economically fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 85 publications
(149 reference statements)
0
13
0
Order By: Relevance
“…Alternative approach for sustainable RA biosynthesis is the implementation of plant in vitro systems. Plant cell cultures give possibilities for the delivery of necessary amount of the targeted bioactive molecules, such as RA, regardless of the vegetative characteristics of the plant species or the limitation of the plant material and the climatic conditions ( Goncalves et al, 2013 ; Marchev and Georgiev, 2020 ). We have previously reported the selection of high RA producing calli cell line PF of Lavandula angustifolia Mill (LV; Georgiev et al, 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…Alternative approach for sustainable RA biosynthesis is the implementation of plant in vitro systems. Plant cell cultures give possibilities for the delivery of necessary amount of the targeted bioactive molecules, such as RA, regardless of the vegetative characteristics of the plant species or the limitation of the plant material and the climatic conditions ( Goncalves et al, 2013 ; Marchev and Georgiev, 2020 ). We have previously reported the selection of high RA producing calli cell line PF of Lavandula angustifolia Mill (LV; Georgiev et al, 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…Extracts from this plant species contain two glycosides: teupolioside and verbascoside. Several studies have demonstrated the potential anticancer, anti-inflammatory, and antioxidant effects of this species, which could, therefore, have cosmeceutical and food production applications [6,7]. Moreover, the presence of phytoecdysteroids (20-hydroxyecdysone) suggests the possible use of Ajuga extract as a botanical pesticide.…”
Section: Introductionmentioning
confidence: 99%
“…The plants naturally produce bioactive compounds when placed in vitro, but its content is very low due to the brief stationary phase that in vitro cultured plants present, because of the inhibition by the action of enzymes [15]. Elicitors such as MeJa and SA are frequently used to enhance the secondary metabolites production in plant cell cultures, since they act as regulators of defense responses, by initiating signals that active multiple secondary biosynthetic pathways and their relevant genes [16,17].…”
Section: Introductionmentioning
confidence: 99%